PEASANTS' SOCIAL ACTION STRATEGIES IN AGRARIAN CONFLICT (STUDY OF THE INDONESIAN PEASANTS' UNION) - Sinaga, Randa Putra Kasea (Journal of Peasants' Rights, 2022)
Movements that are carried out to get resources or desire to achieve social justice, the community needs to regulate the strategies used in carrying out social action. Including for the peasant community in the face of agrarian conflict, as well as SPI (Indonesian Peasants' Union) which organizes peasants' communities facing agrarian conflicts to carry out actions. the struggle for land tenure of conflict. Therefore, it becomes a formulation of the problem in this paper that it is necessary to elaborate and analyze how the dynamics and realities of the use of social action strategies in the face of agrarian conflict by the SPI member peasant community. Using narrative research methods in qualitativeapproaches, this paper is based on the results of research conducted in two SPI base locations, namely Mekar Jaya Village, Wampu Subdistrict. Langkat Regency and Sei Kopas Village Bandar Pasir Mandoge District Asahan Regency, North Sumatra Province. Based on the findings of the study, it is known that the soial action carried out on the study object using strategies that focus on strengthening the mass of action, survives in land occupation, raising support, and weakening of the opposing party.